Non-damage business interruption insurance policies during the COVID-19 pandemic - Marina Brogi; Valentina Lagasio; Fabrizio Santoboni (Economic Review: Journal of Economics and Business, 2022)
Pandemic risks, such as Covid-19, are difficult to insure as they are characterized by multiple factor risks and losses and involve different types of businesses and people simultaneously. The scarcity of time series and statistical data prevents insurers from developing correct pricing. We propose a model of catastrophe risk with Non-Damage Business Interruption (NDBI) policies to manage the pandemic risk due to the spread of Covid-19. The model employs a Monte Carlo simulation of different lockdown scenarios: the frequency and severity distributions of losses of Italian SMEs. The main results show the importance of a Covid-19 lockdown exposure NDBI policy, which benefits not only SMEs but also the insurer.
Keywords: C15; G22; 330; Covid-19; insurance policies; reinsurance; catastrophe risk